The Influence of Intrinsic Motivation on Performance With Work Behavior as A Mediating Variable - Kusuma, Tittis Narulita; Rasyid, Abdul; Pongtiku, Arry (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the influence of intrinsic motivation on performance, the relationship between intrinsic motivation and work behavior, the impact of work behavior on performance, and the relationship between intrinsic motivation and performance through work behavior. The population in this study was all Civil Servants at the Papua Provincial Health Office. The research sample was 146 employees. The sampling technique employed in this study utilized a probability sample with a cluster sampling method. The analysis technique used was the Structural Equation Modeling (SEM) with the assistance of the Moment of Structure Analysis (AMOS) version 26 program. The results of the study indicate that intrinsic motivation has a positive and significant influence on employee performance, intrinsic motivation has a positive and significant impact on employee work behavior, work behavior has a positive and important influence on employee performance and intrinsic motivation has a positive and significant influence on employee performance through employee work behavior.